(2a+3b)(2a-b)-4a(b-a)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 18:48:56
(2a+3b)(2a-b)-4a(b-a)(2a+3b)(2a-b)-4a(b-a)(2a+3b)(2a-b)-4a(b-a)(2a+3b)(2a-b)-4a(b-a)=(4a^2-2ab+6ab-3
(2a+3b)(2a-b)-4a(b-a)
(2a+3b)(2a-b)-4a(b-a)
(2a+3b)(2a-b)-4a(b-a)
(2a+3b)(2a-b)-4a(b-a)=(4a^2-2ab+6ab-3b^2)-(4ab-4a^2)
=4a^2-2ab+6ab-3b^2-4ab+4a^2
=8a^2-3b^2
其中^表示乘方
原式=4a^2-2ab+6ab-3b^2-4ab+4a^2=8a^2-3b^2
(2a+3b)(2a-b)-4a(b-a)
=(4a²-2ab+6ab-3b²)-(4ab-4a²)
=4a²-2ab+6ab-3b²-4ab+4a²
=8a²-3b²
如果要分解
=(2√2a+√3b)(2√2a-√3b)
=4a2+4ab-3b2-4ab+4a2
=8a2-3b2
(2a+3b)(2a-b)-4a(b-a)
=4a²-2ab+6ab-3b²-4ab+4a²
=8a²-3b²
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
2a(a-b)+4a(2a+3b)
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
计算:((a+b)(a-b)-(a-b)^2+2b(a-b))/4(a-b)
-2a(a+b)+b(a+b)
计算:(4a-b)^2-[8a*(a-b)-(3a-b)*(3a+b)]
(2a-3b)[(a+b)-b(a-3b)]
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
a+a-a+2a-3a-2b+3b-5b+3b-4b-5b
计算a^2-b^2/a+b-4a(a-b)+b^2/2a-b
a^2(a-b)+b^2(b-a) 因式分解 (a-b)^3-(a-b)^2 因式分解
A-B A+B 2B+A 3A-B 6A+2B
2(a+3b)²-8(a+b)(a-b)-(a+3b)(a-b)
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
(a-2b)(-2b-a)-(3a+4b)(-3a+4b)